Effect of the COVID-19 Pandemic on Maternal Health in the United States. Issue 2 (March 2023) - Simpson, Kathleen Rice
Abstract : The COVID-19 pandemic is responsible for over 1 million deaths in the United States. More than 500 of those deaths were among pregnant and postpartum women. The recent United States Government Accounting Office report on the effects the pandemic on maternal health is summarized. While the efforts in reporting these data in detail are appreciated, it is past time for taking action to prevent preventable maternal deaths in the United States including the racial and ethnic disparities these deaths represent rather than gathering information about them each year.